AS DIVERSIDADES CULTURAIS NO FUTEBOL BRASILEIRO EM 2015 - da Paz Silva Gomes Amorim, Maria; das Graças Martins Sousa, Maria; Helena Pereira dos Santos, Maria; de Oliveira Gomes, Rejane; Borges Amorim, Rejamara; Magalhães Pontes, Tiago (Revista Form@re - Parfor/UFPI, 2026)
.